Spatial and Temporal Dynamics of Aedes albopictus Populations in Rural and Agricultural Areas in Chania, Greece, After Its Invasion - Stefopoulou, Angeliki; Balatsos, Georgios; Papadopoulos, Nikolaos T.; Daskalakis, Demokritos; Daskalakis, Dimitrios; Chatzidaki, Anna; Milonas, Panagiotis; Papachristos, Dimitrios; Michaelakis, Antonios (Frontiers in Tropical Diseases, 2022)
Aedes albopictus, also known as the Asian tiger mosquito, is an aggressive invasive mosquito species which transmits parasites that cause several major human diseases such as Dengue, Chikungunya, and Zika. Its recent establishment in many European countries and the reported autochthonous cases of Aedes-transmitted arboviral diseases, highlight the importance of effective surveillance programs to plan and implement efficient mosquito-control interventions. Aedes albopictus invaded the Greek island of Crete in 2014 and rapidly spread throughout; however, there are no comprehensive population related data yet available. Our study focused on spatial and temporal dynamics of Ae. albopictus populations in rural and agricultural areas in Chania (western part of the Crete Island). An oviposition surveillance network, consisting of 51 ovitraps was established in 2017 and systematically inspected for two years. Thirty ovitraps were established in rural areas and 21 in the surrounding agricultural areas. Eggs were collected weekly and transferred to the laboratory for counting and assessment of hatching rates. The spatial and temporal egg distribution was assessed by using geographical information systems and spatial statistical analysis tools. Kernel density and hotspot analysis were employed to identify clusters of high populations of eggs. The first and last oviposition activity (eggs in traps) recorded during April-May and December (of both years) respectively, while the maximum egg laying rates were observed during September-October. The proportion of traps with eggs was similar between rural and agricultural areas while the higher number of eggs was recorded in rural compared to agricultural areas during 2017. Egg hatch rates were high (>90%) until end of September. The proportion of diapausing, non-hatched eggs rapidly increased at the end of November. All hatched larvae were identified as Ae. albopictus indicating a negative effect of the invasion on the population of the local species Ae. cretinus. This was the first systematic attempt to monitor the seasonal and spatial patterns of the Asian tiger mosquito in the island of Crete, the southernmost area of Europe and the first study in Europe which assessed temporal and spatial dynamics of Ae. albopictus soon after its invasion in an area.